What gets missed when deploying new technologies in A&E?. - Broome, C.
This paper presents a longitudinal study (over 4 months) of an A&E department where the existing whiteboards were replaced with PC-based computer systems. The study was conducted in two parts-an observation of the physical whiteboard usage and in-depth interviews with all users of both the traditional whiteboard usage and the replacement technology. The research was conducted with the systems manager and all whiteboard users (i.e. nursing management, nurses, doctors, porters and agency staff) across a spread of time frames. Although the technology supported simple information requirements, complex co-ordination, collaboration, and awareness issues were left unsupported. The important role of a pen-holder (information co-ordinator) was poorly supported by the replacement technology as was the task of annotating information with changing situations and needs. Specific deployment issues are derived from these findings that should guide designers when implementing technology replacements for current physical information formats (e.g. whiteboards, notice boards, shared paper notes).
Keywords: Implementation; A&E.